PROSPECTS FOR THE DEVELOPMENT OF ECONOMY DIGITALIZATION IN THE CONDITIONS OF DIGITAL TRANSFORMATION - Zhalilov Rashid Babakulovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article is devoted to the study of activities aimed at the digitalization of the economy in the context of digital transformation. Digitalization and digital transformation of socio-economic systems are considered. The article analyzes the concepts of digital transformation, such as platform, cyber-physical system, new industrial revolution “Industry. 4.0".